TCR-based lineage tracing: no evidence for conversion of conventional into regulatory T cells in response to a natural self-antigen in pancreatic islets - Wong, Jamie (The Rockefeller University Press, 2007)
Foxp3-expressing regulatory T (T reg) cells derive primarily from selection in the thymus. Yet conversion of mature conventional CD4(+) T (T conv) cell lymphocytes can be achieved in several conditions, such as transforming growth factor β treatment, homeostatic expansion, or chronic exposure to low-dose antigen. Such conversion might provide a means to generate peripheral tolerance by “converting” potentially damaging T cells that react to self-antigens. We tested this hypothesis in mice transgenic for the BDC2.5 T cell receptor (TCR), which is representative of a diabetogenic specificity that is naturally present in NOD mice and reactive against a pancreatic self-antigen. In the thymus, before any exposure to antigen, clonotype-positive T reg and T conv cells express a second TCRα chain derived from endogenous loci. High-throughput single-cell sequencing of secondary TCRs of the Vα2 family showed their joining CDR3α regions to be very different in T reg and T conv cell thymocytes. These specific CDR3α motifs, thus, provided a “tag” with which to test the actual impact of T conv to T reg cell conversion in response to peripheral self-antigen; should the autoreactive clonotypic TCR induce T conv to T reg cell conversion upon encounter of cognate antigen in the pancreas or draining lymph node, one would expect to detect tag CDR3α motifs from T conv cells in the T reg cell populations. Sequencing large numbers of peripheral BDC(+)Vα2(+) cells showed that little to no conversion occurs in response to this pancreatic autoantigen.